PERBANDINGAN ISOLASI MINYAK ATSIRI BIJI PALA (Myristica fragrans Houtt) CARA HIDRODISTILASI MICROWAVE DAN KONVENSIONAL SERTA UJI AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN - Rachmi, Widya; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Essential oil of nutmeg (Myristica fragrans Houtt) has been successfully obtained by distillation using conventional and microwave hydrodistillation methods. The essential oil produced by microwave method is more advantageous in yield of oil andcomponents of resulted compounds. The yield of extracted essential oil using microwave method is about 7,07% for 60 minutes higher than that of conventional method which is about 4,30% for 4 hours. Based on the result ofÂ GC-MS analysis,microwave hydrodistillation components obtained 55 compounds more than conventional hydrodistillation as many as 43 compounds in essential oil. The results of antibacterial and antioxidant activity showed that essential oil could inhibit Bacillussubtilis of bacteria and had weak antioxidant activity than of ascorbic acid againtsDPPH radical that is >1000 ug/mL.